Modernising social service delivery in Russia: evolving government support for non-profit organisations. Issue 1 (2nd January 2017) - Benevolenski, Vladimir B.; Toepler, Stefan
ABSTRACT: Russia has recently cracked down on politically active civil society, increasing regulation and undercutting foreign support. However, apolitical, service-oriented parts of civil society have not been subject to these restrictive policies. In contrast, since 2009 Russia has introduced a set of government tools to support socially oriented non-profit organisations. These tools present a framework akin to concepts of 'third-party government' and collaborative governance that have come to dominate Western public administration discourse. This article discusses the Russian government's divergent positions towards civil society, the nature and extent of the supportive tool kit, and its prospects.